Pridobivanje lesa na družinskih kmetijah v Sloveniji - Medved, Mirko (Gozdarski vestnik, 2010)
Timber harvesting is an integral part of the family farms' economy. Nearly a third of forests in Slovenia (total forest area 1.2 mil. ha) are owned by family farms. The average forest property owned by a family farm is three times bigger than any other privately owned forest. General development trendsin the society also affect forest management and the needs of their respective owners. Forest management and use of wood also reflect this developmental impact. Since 2000, forest management and utilization is systematically monitored by the Statistical Office of the Republic of Slovenia: Census 2000 and sample surveys in 2003, 2005 and 2007. In 1990 and 1995, an inquiry among forest owners was performed throughout Slovenia. These results are shown in detail on the level of comparable criteria and indicators: forest owned by family farms, size categories of forest property, roundwood removals, cutting intensity, structure of roundwood use, home use and wood sales. Timber harvesting reflects the need of farms for domestic woodconsumption as well as the need to provide income from the sale of roundwood. An important result are also The analyzes of timber harvesting andwood use with regard to different size categories of forest property showing the structural differences between these categories are an important result, too. Structural differences can indicate the need for different approaches in promoting the intensification of wood production as well as the trends for future harvesting and wood use.
Keywords: pridobivnaje lesa; družinske kmetije; Slovenia; Slovenija